Characterization of gross genome rearrangements in Deinococcus radiodurans recA mutants - Jelena Repar (Nature Portfolio, 2021)
Abstract Genome stability in radioresistant bacterium Deinococcus radiodurans depends on RecA, the main bacterial recombinase. Without RecA, gross genome rearrangements occur during repair of DNA double-strand breaks. Long repeated (insertion) sequences have been identified as hot spots for ectopic recombination leading to genome rearrangements, and single-strand annealing (SSA) postulated to be the most likely mechanism involved in this process. Here, we have sequenced five isolates of D. radiodurans recA mutant carrying gross genome rearrangements to precisely characterize the rearrangements and to elucidate the underlying repair mechanism. The detected rearrangements consisted of large deletions in chromosome II in all the sequenced recA isolates. The mechanism behind these deletions clearly differs from the classical SSA; it utilized short (4–11 bp) repeats as opposed to insertion sequences or other long repeats. Moreover, it worked over larger linear DNA distances from those previously tested. Our data are most compatible with alternative end-joining, a recombination mechanism that operates in eukaryotes, but is also found in Escherichia coli. Additionally, despite the recA isolates being preselected for different rearrangement patterns, all identified deletions were found to overlap in a 35 kb genomic region. We weigh the evidence for mechanistic vs. adaptive reasons for this phenomenon.